PERAN BUDAYA HUKUM DALAM PENGUATAN GOOD GOVERNANCE UNTUK MENDUKUNG AGENDA SDGs - Ali Mukmin (Proceeding International Conference on Social Sciences, 2026)
The role of legal culture in strengthening good governance has become increasingly crucial in realizing the Sustainable Development Goals (SDGs). This normative legal research aims to analyze the extent to which the internalization of legal culture can reinforce the implementation of good governance principles in public institutions. By employing a conceptual and statutory approach, this study reviews relevant legal frameworks and theoretical perspectives that connect the dimensions of legal culture—such as compliance, awareness, and participation—with governance principles of transparency, accountability, and justice. The findings indicate that a strong and progressive legal culture serves as a foundation for the creation of clean, participatory, and just governance practices. Conversely, a weak legal culture often leads to inefficiency, corruption, and lack of accountability. Therefore, strengthening legal culture through education, institutional reform, and legal socialization is an essential strategy in supporting the achievement of SDG 16, which emphasizes peace, justice, and strong institutions.